Implementasi Perjanjian Tura Jaji di Paga Kabupaten Sikka - Antonia Alfiayu Zigha Nanga; Sonia Klara Seke; Ignecya Titania Katoda; Stefanus Don Rade (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Exploring the relationship between contractual law and the local wisdom of "Tura Jaji" is an intriguing subject as it demonstrates how principles of mutual assistance and collective willingness interact with concepts of contractual law governed within a formal legal system. In conducting this research, an empirical method with a sociological approach will be used to observe the relationship between contractual law and the "Tura Jaji" agreement. This study will utilize concrete data or evidence from the real world to understand social phenomena. "Tura Jaji" is one of the cultural practices held by the ethnic Lio community in Ende Regency. The principles embodied in this agreement serve as a moral foundation underlying interactions among individuals, fostering an atmosphere of trust, respect, mutual support, mitigating tribal limitations that often cause divisions, and promoting a sense of unity that solidifies and preserves a cohesive community. "Tura Jaji" is inclusive of an agreement generating obligations between the Lies and Mbengu ethnic groups. It is hoped that both the community and readers actively engage in promoting, supporting, and expanding understanding of the significance of "Tura Jaji" as an inseparable part of daily life. By participating in cultural activities involving "Tura Jaji," collectively, we can ensure that the values embraced within this agreement remain relevant and sustainable within the dynamics of modern society